Obtenção e caracterização físico-química de derivados de yacon (Smallanthus sonchifolius) - Baioco, Flávia Fracalossi (2013)
The yacon is a tuberous root considered a functional food due to the high content of fructooligosaccharides (FOS). In fact to be a perishable food, because of the high water content, processing methods have been proposed to preserve the nutritional constituents and provide its storage. In reason of this, the present study aimed the development and evaluation methods of yacon root processing in order to produce pulpy juice, syrup and flour. For conducting the experiments, first was estimated the best way to extract juice from the root: (i) apply blanching treatment at 100 °C during four minutes, and (ii) do not apply the treatment. Attested the best way to obtain the juice, it was used for the production of juices used in the syrup preparation. The portion of the juice obtained was divided into four fractions, each of them received the following amounts of antioxidants per kilogram of peeled root, respectively: (i) citric acid - 0.18 g, (ii) ascorbic acid - 0.18 g, (iii) a combination of citric acid and ascorbic acid at ratio of 50% each - 0.9 g, and (iv) without the addition of antioxidant. The flour was processed from marc, resulting of juices processing, which was dried at 60 °C and grounded in a blender. Analyses of physicochemical characteristics and color of yacon products were carried out. Obtained data were analyzed statistically by ANOVA and Tukey s test. The bleaching treatment was effective in the juices preparation, because inhibit browning, maintain constant color coordinates and not change the juice physicochemical characteristics. The use of heat in the juice concentration for the syrup preparation not promoted hydrolysis of complex sugars into simple sugars, because reducing glycids did not increase in any of the treatments. Regarding color coordinates, the syrup with citric acid showed higher L* value, indicating greater clarity in relation to others, and also presented the h* value close to 90°, indicating greater proximity to the yellow color, and higher *C value, showing a greater color purity. Flour of yacon marc showed high crude fiber content and, along with control syrup, the higher ash content. Syrups had lower levels of protein, while the flour of yacon marc had the lowest averages of reducing and non-reducing glycids. Thus, in the nutritional and dietary aspects, syrups are preferred due to higher non-reducing glycids, and the syrup with the citric acid antioxidant presented the best color coordinates and pH next to 4.5, making it the best yacon product analyzed in this study